PENGGUNAAN MEDIA BERBASIS KOMPUTER PADA MODEL PEMBELAJARAN DISCOVERY LEARNING - Zelvia Sari; Thamrin Thamrin (Universitas Negeri Padang, 2019)
The purpose of this study is to determine the effect of the use of computer assisted media in discovery learning models to learning outcomes of basic electrical and electronic training courses. The research subject is class X in the expertise of Audio Video (TAV) expertse. this type of research is a quasi-experimental. Students of class X TAV in SMK 1 Ranah Ampek Hulu are 29 school year 2018/2019 and here only take samples from the study as many as 25 students. The data of this study were taken by collecting scores four times through Pretest and Postest with an objective question of 15 items for a single meeting, the question also passed the different test questions, difficulty indexes, validity and reliability. From the four pretest and posttest meetings the results of the study can be seen using the normality test and hypothesis testing. From the results of the study there are average results of the pretest is 60.64 while the posttest is 82.88. The results of the t-test analysis obtained by tcount = 3.738 which is greater than t table = 1.711 at the 0.05 level of significance. Thus it can be concluded that the learning process using powerpoint media has an influence on the learning outcomes of class X TAV students of SMK 1 Ampek Hulu.Keywords: Computer Based Learning, Powerpoint, Discovery Learning (DL)